2021
DOI: 10.1097/wno.0000000000001248
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Ultrasound and Optical Coherence Tomography in Differentiating Between Papilledema and Pseudopapilledema in Children

Abstract: Background: Differentiating between papilledema and pseudopapilledema in children presenting with mild-to-moderate optic nerve head elevation is challenging. This study sought to determine which B-scan ultrasonography (BSUS) and optical coherence tomography (OCT) features, individually or in combination, are best able to differentiate between papilledema and pseudopapilledema in children. Methods: Children presenting with optic nerve head elevation of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…10 A recent study by Farazdaghi et al concluded that optic nerve sheath widening > 4.5 mm on USG has the best sensitivity and speci city for diagnosing papilloedema. 21 The results of our study and Farazdaghi's indicate a better support from USG than SDOCT in ruling out true papilledema in patients suspected to have ONHD on clinical evaluation. We found PHOMS to be more frequently associated with pseudopapilledema, a recent paper by et al also states that PHOMS are seen in 98.4% of children with pseudopapilledema.…”
Section: Discussionsupporting
confidence: 54%
“…10 A recent study by Farazdaghi et al concluded that optic nerve sheath widening > 4.5 mm on USG has the best sensitivity and speci city for diagnosing papilloedema. 21 The results of our study and Farazdaghi's indicate a better support from USG than SDOCT in ruling out true papilledema in patients suspected to have ONHD on clinical evaluation. We found PHOMS to be more frequently associated with pseudopapilledema, a recent paper by et al also states that PHOMS are seen in 98.4% of children with pseudopapilledema.…”
Section: Discussionsupporting
confidence: 54%
“…However, our study observed no change in the NCD before and after HD, suggesting that the rapid changes occurring within a few hours due to HD did not significantly impact the relatively static position of the BMO. PVH can increase in cases of papilledema due to elevated CSF pressure 44 , 45 . A study examining OCT measurements of papilledema in patients with idiopathic intracranial hypertension found correlations with ICP, particularly with maximum height (similar to PVH) 46 , suggesting that PVH measurements in our study could serve as indirect indicators of ICP.…”
Section: Discussionmentioning
confidence: 99%
“…4 While OCT is gaining ground due to its high resolution and availability, [4][5][6] many clinicians continue to rely on earlier technologies, including B-scan ultrasonography, fundus autofluorescence imaging, or fluorescein angiography. [7][8][9][10][11] In short, identification of ODD often remains a clinical challenge, which can benefit from new technologies for improved discrimination from sight-threatening or life-threatening papilledema.…”
Section: Discussionmentioning
confidence: 99%